Forecasting export and import of wheat in Syria using time series (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The aim of this study was to forecast an export and import of wheat in Syria during 2019-2025 using ARIMA models of  time series during period  2000-2018 . The main results were: -The time series for the export of wheat in Syria for the period 2000 - 2018 is unstable, and then stabilized after making the first differences.- ARIMA (1,1,2) model, which is the suitable model to forecast an export of wheat, and expected export will reach to 211.89 ton thousand in 2025.-The time series for the import of wheat in Syria for the period 2000 - 2018 is unstable, and then stabilized after making the first differences.- ARIMA (0,1,2) model, which is the suitable model to forecast an import of wheat, and expected import will reach to 462.45 ton thousand in 2025.